Clinical Features of Anterior Teeth Affected by Molar Incisor Hypomineralization and Treatment Experiences Using Transilluminated Light: A Cross-Sectional Study - Ha, Phạm Thanh; Huyen, Nguyễn Phương; Thanh, Phạm Kim; Hang, Lương Minh; Anh, Trần Tuấn; Ngoc, Võ Như Trương; Anh, Lê Khả; Tuan, Trần Anh; Dong, Tạ Thành (Journal of Dentistry Indonesia, 2024)
Classification and resin infiltration treatment of MIH-related permanent anterior teeth are increasingly receiving attention nowadays. Objective: The study aims to evaluate the characteristics of these teeth; and to assess factors regarding treatment. Methods: A cross-sectional study was conducted using transilluminated and reflected light photographs, and the lesion was classified according to its color, size, type, heterogeneity and surface integrity. The data were analyzed using a chi-square test and multivariate logistic regression analysis to evaluate enamel craze lines (ECL), post-eruptive breakdown (PEB), and treatment procedures. Results: 73 teeth from 46 patients were included, in which 53 teeth had been treated. Size I showed the highest rate of PEB (66.67%). Females (OR = 20.39 (95%CI: 1.62 – 256.18)) and colored lesions (OR = 13.01 (95%CI: 1.82 – 93.13)) were associated with ECL/PEB. Microabrasion and etching cycles were inversely proportional and PEB required 4.33 etching cycles on average. A significant relationship was observed between surface integrity and composite fillings, between yellow/brown spot transformation and lesion color, sex and homogeneity. Conclusion: Lesion color, size, and sex are significant factors influencing ECL and PEB, while sex, surface integrity, lesion color, and homogeneity affect the treatment. Dental practitioners should consider these factors to provide appropriate treatment planning and consultation.